1985
DOI: 10.1007/bf02916546
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH and lysosomal extract on rat liver metallothionein (Cd-thionein)

Abstract: Was studied in vitro. The(109)Cd-labeled protein was isolated by gel filtration and incubated with a lysosomal extract from the same source. No degradation was seen when the pH of the incubation medium was 5 or higher, whereas the degradation of Cd-thionein was completed in 2 h at a pH of 4.5. Dissociation of Cd(2+) from thionein, which takes place to a fair extent at a pH below 5, appears necessary before the enzymatic breakdown of the thionein moiety can take place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Lysosomes probably represent an important subcellular compartment that might be involved in the degradation of MT in vivo: Previous studies on the degradation of MT in rat liver indicated that lysosomes can degrade apo-MT (11,12). However, apo-MT was also shown to be degraded by trypsin, which is a neutral cytosolic protease (11).…”
Section: Resultsmentioning
confidence: 99%
“…Lysosomes probably represent an important subcellular compartment that might be involved in the degradation of MT in vivo: Previous studies on the degradation of MT in rat liver indicated that lysosomes can degrade apo-MT (11,12). However, apo-MT was also shown to be degraded by trypsin, which is a neutral cytosolic protease (11).…”
Section: Resultsmentioning
confidence: 99%